Nilai-Nilai Kemanusiaan dalam Legislasi Hukum Islam di Indonesia - Moh. Dahlan (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2016)
The enforcement of Islamic law has been criticized for being potentially violating human rights as the thinking of BassamTibi. However, this is different with the view of Muhammad Arkoun and Hasan Ash-Syarqawi who received the application of human values in the teaching of Fiqh/Islamic law to be transformed into national law development. Based on these problems, this study can be formulated as follows, how the enforcement of human values can be realized in the development of law in Indonesia. The type of approach of this study is the legal political studies that examined the values of humanity jurisprudence in the development of law in Indonesia. The result of the study shown that the history of the growth and development of Fiqh/ Islamic law is closely related to the actual dynamics of human life, even the existence of the law determined by the interest of human life as well as the views of legal experts, Najmuddin Atu-Tuhfi and Philip K. Hitti. The teachings of. Islamic law have orientation to answer the actual problems of humanity as had been practiced by the Prophet Muhammad and his successors. These human values then get great moment when human rights become a common policy in Universal Declaration of Human Rights (UDHR). In building the system of law in Indonesia, the element of human rights should not be denied and is also an element of legal vacuum at the same time should be considered also, so that the existence of laws that is born from religious or people cultural norms can be accommodated as the applicable legal regulations in Indonesia.